Road Pricing: Old Beliefs, Present Awareness and Future Research Patterns - Edoardo Marcucci (Fondazione Eni Enrico Mattei (FEEM), 1999)
The theoretical evolution of academic beliefs and practical policymakers' perceptions of road pricing (from now on rp) as an instrument of efficient and equitable allocation of resources are described and analysed. The aim of the paper is to reconstruct the logical evolution of the theory behind rp in order to understand why there has been scarce policy impact in spite of a long theoretical tradition. In so doing I try to bring to the fore the fundamental issues that will have to be tackled by future research in order to generate consensus around this policy instrument. The paper is structured in four parts. In the first part the fundamental issues of a typical rp model are considered. Among the most important aspects one recalls: first-best/second-best environment, short/long term analysis, homogeneous/heterogeneous time evaluation, perfect/imperfect information, efficiency/equity analysis, use/non-use of resources generated, private/public transportation provision. In the second part the characterising parameters have been interpreted in the light of the Smeed Report of 1964 that can be considered representative of the "old belief". In the third part the "present awareness" is expressed by an analysis of the main contents of the book Internalising the Social Costs of Transport of 1993. In the fourth part some reflections on the most promising research areas for rp implementation and acceptance are put forward. Specific research will have to be conducted concerning social acceptability and feasibility, simultaneous cost internalisation, behavioural assumptions, information and pricing interconnections.
Keywords: R41; R48; 330; Road pricing; Social Acceptability; Congestion; Congestion charging; Straßenbenutzungsgebühr; Verkehrsstau; Theorie